Economic potential of seagrasses in Sirahan-IKI, Taklong Island, Nueva Valencia, Guimaras. - Niego, Allen Grace
Seagrasses are essential part of marine ecosystem due to their productivity level. Seagrass beds provide food, shelter, and ideal environment for juvenile fishes and invertebrates to conceal themselves from predators. They also act as sewage filter, thus maintaining water clarity by trapping fine sediments and other particles in their. Seagrasses stabilize the sea bottom with their roots and rhizomes and give protection to the infaunal organisms living within the substratum. They also dampen the effects of strong currents, preventing the scouring of bottom areas and provide attachment sites for the epiphytes., This study is generally intended to determine the economic potential of seagrass communities in Taklong Island, Nueva Valencia, Guimaras. It is specifically aimed to identitfy marine species found in seagrass beds that can be consumed for food, and assess its economic importance and monetary value per species and per sampling. The sampling was done in Sirahan-iki, Taklong Island every two weeks from the period of November 2005 to January 2006 for a total of 7 samplings. Gill nets (mesh size of 2" x 2") were used in the sampling. the species caught were identified down to the Genus level. Each individual caught was weighed and measured in terms of total length. The relative frequency and relative abundance of the caught species were also computed while the length and weight of the species were correlated. Results of the study showed that 95.83 percent of the total catch are fishes and only 14.17 percent is crustacean, specifically Portunus pelagicus. The most abundant of the of the fishes is the Siganus canaliculatus wth the relative abundance of 20.83 percent and had appeared 5 times out of the total 7 samplings with relative frequency of 23.81 percent. It was followed by Liza vaigiensis which appeared three times out of the 7 samplings with a relative frequency of 14.29 percent. The results of the survey showed that most fishermen were aware of the importance of seagrass in the ecosystem. They fish in the seagrass community twice a month with the use of gill nets most of the time. The most frequently caught species was Siganus canaliculatus , which was sold to the market with pricesranging from 40-50 pesos followed by Liza vaigiensis. The moneytary value per sampling ranges from 0 to 744.72.